помогите преобразовать в многочлен выражение: (x-1)^2-2(x-2)(x-1)

срочно плз!!!

2

Ответы и объяснения

  • Участник Знаний
2013-08-30T15:45:01+00:00
= X^2 - 2X + 1 - 2*(X^2 - X - 2X + 2) = X^2 - 2X + 1 - 2X^2 + 2X + 4X - 4 =
= - X^2 + 4X - 3 
терерь можно и разложить:
D = 16 - 4*(-1)*(-3) = 16 - 12 = 4
X1 = ( - 4 + 2) \ - 2 = - 2 \ - 2 = + 1
X2 = - 6 \ - 2 = + 3
Ответ:  - X^2 - 4X + 3 или =  (Х - 1)*(X - 3)
2013-08-30T15:51:46+00:00
(x-1)^2-2(x^2-x-2x+2)=(x-1)(x+1)-2x^2-2x-4x+2=x^2-x-x-1-2x^2-2x-4x+2=-x^2-8x+1